Community Engagement in Tourism Management: A Holistic Perspective from Bangladesh - Farhan, Kazi Ahmed; Mohiuddin, Muhammad (Global Disclosure of Economics and Business, 2026)
The study made an inquiry into the core potentials of community engagement in tourism management of Bangladesh with special focus on a holistic perspective. We know that community engagement in tourism management anywhere in the world gives improved uptake of services and increased outcomes. Community engagement in tourism management is examined holistically in Bangladesh’s tourism scenario. The study uses secondary data from published journal articles, books, reports, and firms’ documents to make discussions, findings, and recommendations. Significant findings show that while community engagement in tourism is low, more inclusive techniques can have beneficial results. The challenges found are unequal distribution of economic advantages, poor governance, environmental deterioration from uncontrolled tourism, and insufficient local community capacity-building. The research calls for comprehensive policy reforms recognizing communities as vital stakeholders, providing equal economic opportunity, strengthening governance, and improving environmental conservation. Fostering public-private-community participations and using technology for inclusion are essential policy proposals. In conclusion, the study recommends an integrated tourism management model that empowers local people, distributes benefits fairly, and assures Bangladesh’s tourism sector’s long-term viability to sustain.